Utilization of 2D photography for acquisition of facial anthropometry / Sayfaldeen Kashmoola ... [et al.] - Kashmoola, Sayfaldeen; Tengku Mohd Ariff, Tengku Fazrina; Abdul Wahab, Hazmyr (Universiti Teknologi MARA Cawangan Pulau Pinang, 2020)
Anthropometry is defined as the scientific study of the measurements and proportions of the human body. To date, the most used methods for the acquisition of facial anthropometric parameters are direct method employing calipers and protractors tools, which are time-consuming, or indirect methods employing three-dimensional (3D) imaging systems, which are expensive. Despite the possible advantages of two-dimensional (2D) photography, it is not widely explored due to complications such as resolution and distortion of digital photos. The objective of this study is to assess the accuracy of the Digital Single-Lens Reflector (DSLR) camera as an indirect method against direct method at different aperture and distance to subject. Adults aged 20-45 years were voluntarily recruited in this study (n=24). Twelve facial anthropometric parameters were measured for each participant using direct anthropometry (sliding caliper), and indirect anthropometry (DSLR camera). When placing the DSLR camera at 2.0 meters from subjects with f/6.3 aperture, nine facial anthropometric parameters were obtained accurately (p> .05). The findings suggested that the accuracy of the DSLR camera as an indirect method for the acquisition of facial anthropometric parameters was established at the aperture setting of f/6.3 and the object distance at 2.0 meters. Therefore, it can be recommended as a facial anthropometry acquisition technique.